2017
DOI: 10.1186/s12864-017-4157-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Citrobacter werkmanii strain BF-6 isolated from industrial putrefaction

Abstract: BackgroundIn our previous study, Citrobacter werkmanii BF-6 was isolated from an industrial spoilage sample and demonstrated an excellent ability to form biofilms, which could be affected by various environmental factors. However, the genome sequence of this organism has not been reported so far.ResultsWe report the complete genome sequence of C. werkmanii BF-6 together with the description of the genome features and its annotation. The size of the complete chromosome is 4,929,789 bp with an average coverage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…This study examined the expression of six biofilm-related genes as well as slt-II and viaB , based on the primers listed in Table 4 , which were derived from earlier studies [ 81 , 85 , 114 , 115 ]. The genes bsmA , bssR , bssS and csgD were reported to contribute to planktonic and biofilm growth in Citrobacter werkmanii BF6 [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the expression of six biofilm-related genes as well as slt-II and viaB , based on the primers listed in Table 4 , which were derived from earlier studies [ 81 , 85 , 114 , 115 ]. The genes bsmA , bssR , bssS and csgD were reported to contribute to planktonic and biofilm growth in Citrobacter werkmanii BF6 [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genes bsmA, bssR, bssS and csgD were reported to contribute to planktonic and biofilm growth in Citrobacter werkmanii BF6 [114]. The genes tabA and hmsP were identified as biofilm related in a subsequent study on the same organism [115]. The gene bsmA (biofilm stress and motility) or biofilm peroxide resistance protein, known as yjfO in E. coli, is upregulated during biofilm growth [116] Mutant analysis revealed roles in microcolony formation, flagellar motility as well as resistance to acid and peroxide stresses [116].…”
Section: Polymer Adhesion and Gene Expressionmentioning
confidence: 95%
“…The results showed that deletion of hutZ Ep led to a substantial decrease in the thickness and density of the biofilm during biofilm formation compared to those of the parental strain (Figure 7C). To explore whether hutZ Ep was directly related to E. piscicida biofilm formation, the expression of several biofilm-related genes, such as bsmA , bssS , hmsP , and csgD [43], was investigated by RT-qPCR, and the results showed that the expression of these biofilm-related genes remained unchanged when hutZ Ep was deleted (data not shown). These findings indicated that HutZ Ep directly participates in biofilm growth and is probably a novel biofilm-related factor.
Figure 7 Effects of hutZ Ep mutation on biofilm growth.
…”
Section: Resultsmentioning
confidence: 99%
“…The Citrobacter species belong to the domain Bacteria [ 1 ], the phylum Proteobacteria [ 2 ], the class Gammaproteobacteria [ 3 ], the order Enterobacteria [ 4 ], the Enterobacteriaceae family [ 5 ] and Citrobacter genus [ 6 ], and was introduced in 1932 by Werkman and Gillen [ 7 ]. The Citrobacter genus typically utilizes citric acid as the primary carbon source [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%